King breaks fast with UMP students, staff - UMP, PNC (The Sun Daily, 2023)
KUANTAN: Yang di-Pertuan Agong Al-Sultan Abdullah Ri’ayatuddin Al-Mustafa Billah Shah today joined a breaking of fast event with staff and students of Universiti Malaysia Pahang (UMP) here.